Cathodic reduction of glucose - Kassim, Annvar; Rice, Colin L.; Kuhn, Anselm T. (1981)
The cathodic reduction of D-glucose was studied on Pb, Ni, Zn and Cd cathodes at three pH values in aqueous solution. The effect of cathode geometry and flow rate were also examined. Partial reduction current densities were obtained by g.l.c. analysis of the derivatised products. Current interruption and resumption, as well as runs using pretreated and untreated cathodes, all tend to suggest the presence of a surface film formed on the cathode during reductions. From these results and a re-interpretation of the data of other workers, a mechanism is proposed involving the near-electrode surface pH change, with the Tafel slope and reaction rate further altered by the solid formed at the cathode surface.